Peran Pendidikan Agama Islam Dalam Memproteksi Peserta Didik Dari Paparan Konten Homoerotik Di Media Sosial: Studi Kasus Peserta Didik Kelas VII Sekolah Menengah Pertama Negeri 1 Paseh Kabupaten Bandung - Amelia, Nina; Mukhlishah; Muhtadin; Ibrohim, Iim; Hernawati (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
The LGBTQ+ phenomenon has rapidly developed by utilizing social media as a platform to showcase its existence, including homoerotic content that features same-sex romance and is widely spread on social media. This can have negative moral and psychological impacts, especially on students. Islamic Education plays an important role in protecting students from this negative content. Through religious education, students can better understand Islamic religious and moral values, enabling them to guard themselves against negative content on social media. This study aims to analyze the homoerotic phenomenon at SMPN 1 Paseh, the role of Islamic Education, the supporting and inhibiting factors, and the outcomes of the role of Islamic Education in protecting students from exposure to homoerotic content on social media. This research uses a qualitative approach with case studies and descriptive methods. Data were collected through observation, interviews, and documentation. Participants consisted of five students and three teachers. The results of the study show that the role of Islamic Education provides positive outcomes by helping students build self-awareness of the laws and effects of homoerotic content, leading them to avoid and reject such content.